Molecular Biology and Genetics Research on Schizophrenia - Shi, Chongwei (International Journal of Public Health and Medical Research, 2024)
Schizophrenia is a severe mental disorder characterized by a complex etiology involving genetic, environmental, and neurobiological factors. Recent advances in molecular biology and genetics have provided crucial insights into the pathogenesis of schizophrenia. This paper reviews the fundamental concepts and etiological theories of schizophrenia, with a detailed examination of the applications of molecular biology and genetics in schizophrenia research, particularly focusing on the latest developments in genomics and genetic susceptibility studies. By analyzing the functions of known relevant genes and exploring gene-environment interactions, this paper reveals the complex molecular mechanisms underlying schizophrenia and discusses future research directions. Our research indicates that integrating modern molecular biology techniques and genetic methods will aid in early diagnosis and precise treatment of schizophrenia, advancing clinical applications and optimizing public health strategies.